Influence of an interview location on opinions about the ecosystem services provided by trees - Matczak, Piotr; Mielewczyk, Marcin; Mączka, Krzysztof; Przewoźna, Patrycja; Inglot, Adam (Quaestiones Geographicae, 2024)
Collecting opinions regarding environmental management is essential, particularly in urban areas where space is limited, and interests often collide. However, the impact of the conditions in which the research is conducted on opinions and preferences elicited via surveys and interviews about the environment is usually taken for granted. The recent development of computer-aided survey methods allows a simulation of an environment, which can create an artificial environment for interviews. Therefore, examining whether direct access to the environment impacts opinions and preferences becomes a significant issue when considering environmental policies and management design and execution. This study examines whether the location of an interview, indoors or outdoors (in the vicinity of trees), influences the opinion on the ecosystem services (ES) trees provide. A quasi-experimental method with a map-aided computer-assisted personal interview (CAPI) survey in two Polish cities, indoors and outdoors, in the vicinity of trees, shows that respondents’ location did not significantly affect the opinion on the ES provided by trees. However, on average, respondents answering the survey inside buildings marked more trees on a map than those answering outside. We argue that although an interview location does not have a significant impact on the results, from the perspective of various stakeholder groups in participatory processes, the convenience of place is more important than the character of the place (i.e., in the vicinity of trees) as long as the survey method is mediated by a virtual representation of the subject of the study.